Migrants’ regrets: The role of regulatory focuses, social comparison, discrimination, and uncertainty aversion - Kosic, Ankica; Leder, Susanne; Pica, Gennaro (Psychology Hub, 2024)
In this study, we examined regrets of migrants and focused on three factors that may enhance regret about the decision to emigrate: regulatory focus, social comparison with co-nationals in the country of origin, and perceived discrimination. The study involved 196 first generation immigrants in the UK originated from different countries. A questionnaire was used containing scales measuring individual’s regulatory focus, social comparison with co-nationals in the country of origin, perceived discrimination, feeling of uncertainty, and regret. The more prevention-focused migrants are, the more they regret their decision to emigrate. Furthermore, upward social comparison with co-nationals in the home country and perceived discrimination are related to stronger regret. Basically, the more people negatively compared themselves with co-nationals in the country of origin, the more they experienced regret about their decision to emigrate. In addition, we found some interaction effects. The relationship between prevention focus (vs. promotion focus) and regret is stronger for migrants who make negative comparisons with co-nationals in the country of origin, perceive that they are discriminated against, and who are more averse towards uncertainty.